Therapy Compliance Level of Chronic Kidney Failure Patients With Hemodialization In The Hemodialization Room - Wahyu Tanoto; Moch. Zaenal B. (Journal of Applied Nursing and Health, 2022)
Background: Chronic kidney failure (CKD) is a functional disorder. Chronic kidney disease is progressive and irreversible. Hemodialysis is a technology for kidney function therapy to remove metabolic wastes or toxins from the body. Compliance is the level of accuracy of a person's behavior. This study aimed to determine the level of adherence to therapy for chronic kidney failure patients with hemodialysis in the hemodialysis room at Mardi Waluyo Hospital, Blitar. Methods: The method used in this research is descriptive. The population in this study was 121 respondents. The research sample was 17 respondents. This study uses a "purposive sampling" technique. The research variables were CKD patients with hemodialysis therapy, and the data collection technique used a questionnaire Results: From the data that had received HD information or did not show all of the respondents received HD information, 17 respondents (100%), and none of the respondents who did not receive HD information, 0 respondents (0%).The results showed that all respondents, namely 17 (100%), were obedient in carrying out hemodialysis therapy Conclusion: It is hoped that health workers can determine the level of adherence to therapy for patients with chronic kidney failure with hemodialysis to provide maximum care for patients with chronic kidney failure